2006
DOI: 10.1111/j.1447-0756.2006.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone replacement therapy regimens on mammographic breast density: The role of progestins

Abstract: Postmenopausal HRT may increase mammographic breast density. Breast density appears to be mostly affected by higher doses and continuous administration of progestin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…These observations are in line with numerous earlier studies showing similar significant increases in breast density with treatment with continuously combined estrogen plus progestin [18][19][20][21][22][23][24] . Increases in breast density cannot be related to one particular combination or progestin per se, because similar observations were reported from trials testing combinations with norethisterone acetate, medroxyprogesterone acetate or micronized progestin 18,23,25 .…”
Section: Clinical Aspectssupporting
confidence: 93%
“…These observations are in line with numerous earlier studies showing similar significant increases in breast density with treatment with continuously combined estrogen plus progestin [18][19][20][21][22][23][24] . Increases in breast density cannot be related to one particular combination or progestin per se, because similar observations were reported from trials testing combinations with norethisterone acetate, medroxyprogesterone acetate or micronized progestin 18,23,25 .…”
Section: Clinical Aspectssupporting
confidence: 93%
“…Breast cancer is a multifactorial disease which is believed to be related to a number of risk factors such as age, nulliparity or first pregnancy at older age, genetic predisposition (BRCA1, BRCA2), personal and family history of breast cancer, previous abnormal biopsy results, mammographic density, obesity, radiation, early onset of menarche, alcohol, smoking, and hormone therapy [22,35,39,46,72]. After age and BRCA1/2 genetic predisposition, high mammographic density is the third largest population risk factor for subsequent development of in situ or invasive carcinoma ( [8,9,49].…”
Section: Possible Relationship Of Ccls To Mammographic Densitymentioning
confidence: 99%
“…111 Interestingly, there also seems to be a dose dependency for HRT as shown in a study where increased risk was observed in 60% of those receiving higher doses of progestin compared with 16.7% in those receiving a lower dose. 3 Increased risk has also been reported to be dependent on regimens, i.e. higher in those using cc HRT (39%) compared with those using cyclic HRT (15%) or unopposed oestrogen (<5%).…”
Section: Breast Cancermentioning
confidence: 96%
“…increased risk for coronary heart disease (CHD), breast cancer, venous thromboembolism (VTE) and stroke. 2 Interestingly, some literature indicate at least for some of the caveats, a dose dependency for HRT, [3][4][5][6][7][8] as well as a dependency of the particular type of hormone used. 6,[8][9][10] We review the literature on these issues and the rationale behind recommendations from authorities 11,12 and menopause societies 13,14 that women deemed in need of HRT should receive the lowest possible dose of oestrogen and progestogen.…”
Section: Introductionmentioning
confidence: 98%